2020
DOI: 10.1200/jco.2020.38.15_suppl.12009
|View full text |Cite
|
Sign up to set email alerts
|

A geriatric assessment (GA) intervention to reduce treatment toxicity in older patients with advanced cancer: A University of Rochester Cancer Center NCI community oncology research program cluster randomized clinical trial (CRCT).

Abstract: 12009 Background: GA evaluates aging-related domains (e.g., function) known to be associated with cancer treatment toxicity. In this CRCT, we evaluated if providing a GA summary with management recommendations to oncologists can reduce toxicity in older patients (pts) with advanced cancer receiving chemotherapy and/or other agents with a high reported prevalence of grade 3-5 toxicity. Methods: Pts aged > 70 with incurable solid tumors or lymphoma and > 1 impaired GA domain starting a new treatment regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 0 publications
0
75
0
Order By: Relevance
“…Although GA‐guided interventions are effective for improving survival and functional status in several scenarios [2], there is a lack of information regarding the effects of GA‐guided care on traditional “hard” oncological outcomes, such as overall survival (OS), treatment toxicity, or quality of life (QoL) [3]. Fortunately, four randomized clinical trials (RCT) presented at the 2020 ASCO Annual Meeting have provided new evidence showing that the implementation of GA‐guided interventions for older adults with cancer can in fact lead to improvements in QoL and decreased treatment toxicity, without compromising survival (Table 1) [ 4–6]. These RCTs represent a giant leap forward for geriatric oncology, because they provide a strong foundation that will allow for GA‐guided interventions to become the standard of care for all older adults with cancer.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Although GA‐guided interventions are effective for improving survival and functional status in several scenarios [2], there is a lack of information regarding the effects of GA‐guided care on traditional “hard” oncological outcomes, such as overall survival (OS), treatment toxicity, or quality of life (QoL) [3]. Fortunately, four randomized clinical trials (RCT) presented at the 2020 ASCO Annual Meeting have provided new evidence showing that the implementation of GA‐guided interventions for older adults with cancer can in fact lead to improvements in QoL and decreased treatment toxicity, without compromising survival (Table 1) [ 4–6]. These RCTs represent a giant leap forward for geriatric oncology, because they provide a strong foundation that will allow for GA‐guided interventions to become the standard of care for all older adults with cancer.…”
Section: Figurementioning
confidence: 99%
“…In the GAP‐70 cluster RCT, investigators from the University of Rochester analyzed the effect of providing GA‐guided recommendations to oncologists working in community practices [4]. Forty‐one practices were randomized to the GA intervention or to usual oncologist‐directed care alone.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a recent study indicates that when the GA is not taken into account for prescribing chemotherapy, 34% of unfit patients are overtreated, which is associated with more grade 3-4 toxicity than those receiving treatment adapted to fragility (42% vs. 31%; p < 0.05) (9). In addition, recently, two randomized clinical trials evaluating the impact of GA vs. standard of care on chemo toxicity in older adults with cancer showed the integration of multidisciplinary GA-driven interventions reduced the incidence of grade 3-5 chemo-related toxicity by 10-20% [37,38].…”
Section: Frailty In Elderly Patients With Metastatic Crcmentioning
confidence: 99%
“…Until recently, no randomized trial had yet to demonstrate that GA-guided care interventions definitively improve outcomes in older adults with cancer, despite these interventions improving outcomes in older non-cancer populations [45]. However, at the 2020 ASCO virtual meeting, 3 randomized trials were presented and demonstrated GA-based interventions helped improve quality of life and toxicity rates among older adults receiving systemic therapy without decreasing expected survival [27,46,47]. Additionally, to help clinicians better identify frailty, a frailty index (scoring system) generated from the results of GA has been designed that is predictive of all-cause mortality, reduced health-related quality of life, and hospitalizations [48][49][50].…”
Section: Geriatric Assessmentmentioning
confidence: 99%